Cloud-based design and manufacturing: A new paradigm in digital manufacturing and design innovation. (February 2015) - Wu, Dazhong; Rosen, David W.; Wang, Lihui; Schaefer, Dirk
Abstract: Cloud-based design manufacturing (CBDM) refers to a service-oriented networked product development model in which service consumers are enabled to configure, select, and utilize customized product realization resources and services ranging from computer-aided engineering software to reconfigurable manufacturing systems. An ongoing debate on CBDM in the research community revolves around several aspects such as definitions, key characteristics, computing architectures, communication and collaboration processes, crowdsourcing processes, information and communication infrastructure, programming models, data storage, and new business models pertaining to CBDM. One question, in particular, has often been raised: is cloud-based design and manufacturing actually a new paradigm, or is it just "old wine in new bottles"? To answer this question, we discuss and compare the existing definitions for CBDM, identify the essential characteristics of CBDM, define a systematic requirements checklist that an idealized CBDM system should satisfy, and compare CBDM to other relevant but more traditional collaborative design and distributed manufacturing systems such as web- and agent-based design and manufacturing systems. To justify the conclusion that CBDM can be considered as a new paradigm that is anticipated to drive digital manufacturing and design innovation, we present the development of a smart delivery drone as an idealized CBDM example scenario and propose a corresponding CBDM system architecture that incorporates CBDM-based design processes, integrated manufacturing services, information and supply chain management in a holistic sense. Highlights: We present a new paradigm in digital manufacturing and design innovation, namely cloud-based design and manufacturing (CBDM). We identify the common key characteristics of CBDM. We define a requirement checklist that any idealized CBDM system should satisfy. We compare CBDM with other relevant but more traditional collaborative design and distributed manufacturing systems. We describe an idealized CBDM application example scenario.